The antique heros in the european historical novel - Aliyev, A.R. (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The issues of the ancient heros are investigated in the article. They said different thoughts about the historical novel in the world literary criticism. So, the terms as «the historical novel», «the novel which told about history », «the novel which based in the history», «the novel of the history» have been used about this kind of novels. The historical novels which talked about distant historical periods are researched in this article. To this group of historical novels we can show the well-known English writers Edward George Earle Lytton Bulwer-Lytton’s «The Last Days of Pompeii» and Robert Graves’ «I, Claudius»; the prominent French writers Gustave Flaubert's «Salammbô» and Maurice Samuel Roger Charles Druon’s; «The novel about Alecsandr Macedonian or God»; the notable german writer Goerg Ebers’ «Ward»; italian writer Raffaello Giovagnoli's «Spartaco»; the well-known Henryk Sienkiewicz’s «Where is your way?» («Quo vadis») and Boleslav Proust’s «Pharaoh» as an example in European literature.
Еуропалық тарихи романның көне кейіпкерлері
Античные герои в европейском историческом романе
Keywords: antique heros; historical novels; ancient times; Salammbo; Spartacus; Robert Graves